2016
DOI: 10.1055/s-0036-1593612
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Disease-Specific Questionnaire for Basal Joint Arthritis

Abstract: The Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire is the most commonly used instrument to assess outcomes of basal joint arthritis (BJA). However, the DASH is subject to influence by the entire upper extremity. This study aims to develop and validate a disease-specific questionnaire for BJA that would be more sensitive to changes in thumb function and pain, and correlate better with objective and subjective metrics. The thumb disability examination (TDX) was developed and 80 patients present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 41 publications
0
38
0
7
Order By: Relevance
“…The original questionnaire showed value for internal consistency with α > 0.79. 10 No ceiling or floor effect was found in the questionnaire or in the subdivisions. The number of questions and the presence Rev Bras Ortop of many alternatives reduce the possibility of this effect.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The original questionnaire showed value for internal consistency with α > 0.79. 10 No ceiling or floor effect was found in the questionnaire or in the subdivisions. The number of questions and the presence Rev Bras Ortop of many alternatives reduce the possibility of this effect.…”
Section: Discussionmentioning
confidence: 84%
“…Noback et al 10 proposed a specific questionnaire for rhizarthrosis, the TDX, in order to improve accuracy when comparing therapeutic outcomes. 10,11 The questionnaire evaluates activities performed by patients in the last week and the 20 items are divided into 3 subdivisions, all graded in 5 degrees (following the Likert Scale , where N is the total sum, Q is the number of total questions and B the number of questions left blank.…”
Section: Methodsmentioning
confidence: 99%
“…When the TDX was first validated, Noback et al reported an average completion time of 134 seconds, whereas it took approximately 7 minutes to complete the DASH score. 12,18 The TDX therefore lends itself to greater compliance as patients and physicians are more willing to complete a questionnaire fully that is brief and specific for BJA. Grip strength has shown higher significant correlation with CMC joint osteoarthritis (p < 0.001) compared with pinch strength (p ¼ 0.049) in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The TDX score and associated validation procedures were subsequently published in 2017. 12 Based on the validation of the questionnaire in 65 patients, it was reported to be a quick, easy, and reliable tool that could be assessed in approximately 2 minutes and correlated strongly with grip strength (p < 0.01), A-VAS (p < 0.01), and DASH score (p < 0.001). 12 The primary purpose of this study was to further evaluate whether the TDX is a reliable, sensitive, and disease-specific tool for BJA.…”
mentioning
confidence: 99%
See 1 more Smart Citation